Kenpaullone (CDK2 Inhibitor dan GSK-3? Inhibitor) sebagai agen otoprotektif pada pasien kemoterapi berbasis cisplatin: tinjauan pustaka - Ida Bagus Wisnu Widiarta; Anbiya Khairul Umam; I Putu Santhi Dewantara (DiscoverSys Inc., 2020)
Background: Malignancies are one of the diseases with the most sufferers, almost all country in the world has a number of these diseases. Cisplatin-based chemotherapy regimens have long been the gold standard in the treatment of various soft tissue malignancies. Despite many beneficial cisplatin features, it also has serious side effects, which are nephrotoxicity, neurotoxicity, and ototoxicity. This literature study aims to theoretically review the role of kenpaullone (CDK2 Inhibitor and GSK-3? Inhibitor) as an autoprotective agent in cisplatin-based chemotherapy patients.Methods: The literature review approach is used in this study. Sources of reading come from relevant and appropriate journals and books from PubMed and Google Scholar.Results: Cisplatin is thought to selectively damages the outer hair cells within the organ of Corti, spiral ganglion cells, and cells within the stria vascularis. It is reducing the formation of free radicals as otoprotective strategies by maintaining glutathione levels and antioxidant activity. Kenpaullone provided significant protection against cisplatin-induced ototoxicity when delivered by tran tympanic injection in zebrafish, mice, and rats. Kenpaullone has proven to directly inhibit cyclin-dependent kinase 2 (CDK2) and Glycogen synthesis kinase-3, thereby attenuating cisplatin-induced mitochondrial ROS production caspase 3/7-mediated cell death. Cisplatin can cause ototoxicity in the manifestation of hearing loss; thus, an otoprotector is needed to prevent this side effect. Kenpaullone is a CDK2 inhibitor and GSK-3 inhibitor that can reduce damage to outer hair cells induced by cisplatin to prevent ototoxic hearing loss.Conclusion: The results of this study indicate that various literature studies show that kenpaullone (CDK2 Inhibitor and GSK-3? Inhibitor) can be used as an autoprotective agent in cisplatin-based chemotherapy patients. Latar Belakang: Keganasan merupakan salah satu penyakit yang memiliki jumlah pasien terbanyak, hampir seluruh negara di dunia memiliki jumlah penderita penyakit tersebut. Kemoterapi berbasis cisplatin telah lama menjadi baku emas untuk terapi pada beberapa keganasan jaringan lunak. Selain memberikan banyak keuntungan, cisplatin juga menimbulkan efek samping yang berat seperti nefrotoksik, neurotoksik, dan ototoksik. Studi tinjauan pustaka ini bertujuan untuk meninjau secara teoritis peran kenpaullone (CDK2 Inhibitor dan GSK-3? Inhibitor) sebagai agen otoprotektif pada pasien kemoterapi berbasis cisplatin.Metode: Dalam penulisan ini digunakan metode tinjauan pustaka. Sumber bacaan berasal jurnal-jurnal dan buku-buku yang relevan dan sesuai dari PubMed maupun Google Scholar.Hasil: Diduga bahwa cisplatin secara selektif merusak bagian sel luar disertai organ korti, sel ganglia spiral, dan sel dengan stria vaskularis. Strategi otoprotektif termasuk menurunkan pembentukan radikal bebas dengan menjaga level gluthione dan aktivitas antioksidan. Kenpaullone memberikan efek protektif signifikan terhadap ototoksisitas akibat terapi cisplatin ketika dinjeksikan secara transtimpani pada ikan zebra, dan tikus. Kenpaullone terbukti secara langsung menginhibisi Cyclin-Dependent Kinase 2 (CDK-2) dan Glycogen Synthesis Kinase-3 (GSK-3), menurukan produksi ROS mitokondria yang diinduksi oleh cisplatin serta caspase 3/7 yang memediasi kematian sel. Sehingga hal tersebut dapat mencegah terjadinya gangguan pendengaran akibat ototoksik.Kesimpulan: Hasil tinjauan pustaka ini menunjukkan bahwa berbagai studi literatur menunjukkan bahwa kenpaullone (CDK2 Inhibitor dan GSK-3? Inhibitor) dapat dipergunakan sebagai agen otoprotektif pada pasien kemoterapi berbasis cisplatin.